Mengevaluasi Interaksi Manusia Dan Komputer Pada Website E-Learning Universitas Singaperbangsa Karawang Menggunakan Metode Webqual 4.0 - Rizqillah, Fathulfiqri; Voutama, Apriade; Ridha, Azhari Ali (Peneliti.net, 2023)
This study aims to evaluate human and computer interaction on the e-learning website of Singaperbangsa University Karawang. The university uses the website as a medium to support lecture activities. The evaluation was carried out by considering aspects of e-learning website quality, user satisfaction, and WebQual 4.0 quality assessment methods. This research also implements the paradigm of human and computer interaction in application/website design. The results of this study are expected to provide insights and recommendations to improve human-computer interaction on the University of Singaperbangsa Karawang e-learning website.